Electrolyzer system and method of electrode manufacturing

By using a substrate design in the electrolyzer system with bipolar plates, porous transport layers, and catalysts, combined with nitrogen-assisted hydrogen production technology, the stability and cost issues of the electrolyzer system were solved, achieving more efficient and stable hydrogen production.

CN121241167APending Publication Date: 2025-12-30SUNGREENH2 PTE LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480020907.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-23
Filing Date
2024-01-23
Publication Date
2025-12-30

AI Technical Summary

Technical Problem

Existing electrolyzer systems suffer from insufficient stability and high electrode material costs. A method is needed to reduce the power burden and electrode material costs while maintaining or improving their efficiency.

Method used

An electrolyzer system is employed, comprising a bipolar plate, a porous transport layer, and a catalyst. The substrate is formed by sintering a metal-polymer mixture, and conductive and alloy materials are used to reduce dependence on platinum group metals. Combined with nitrogen-assisted hydrogen production technology, oxygen release is avoided, thereby improving system stability.

Benefits of technology

By splitting water or nitrogen compounds at lower voltages, the efficiency and long-term stability of electrodes and MEAs are improved, the demand for PGM is reduced, the risk of H2 and O2 gas mixture explosion is avoided, and high cell current density and long-term continuous operation stability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121241167A_ABST
    Figure CN121241167A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyzer system and a method of electrode manufacturing. The electrolyzer system may include a first vessel in communication with the electrolyzer stack, a power source, an electrode, a separator, a membrane, and a second vessel in communication with the electrolyzer stack. The electrode may include a catalytic material and a microporous and / or nanopore structure. A method of electrode fabrication may include providing a substrate, contacting the substrate with an acidic solution, applying an electrical current to the substrate while depositing a primary material and a support material comprising a sacrificial material onto the substrate, and leaching the sacrificial material.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-reference to related applications

[0001] This application claims priority and benefit to U.S. Provisional Patent Application No. 63 / 440,690, filed January 23, 2023, entitled “Method for Manufacturing Electrolyte Systems and Electrodes,” the description of which is incorporated herein by reference. Invention Field

[0002] Embodiments of the present invention relate to an electrolyzer system for producing gaseous hydrogen, having an anode, a cathode, and / or an ion exchange membrane separating the anode and cathode. The electrolyzer system is powered by a renewable energy source, including solar, wind, hydro, bioenergy, and geothermal energy. Background of the Invention

[0003] Hydrogen is a crucial part of any discussion about sustainability and emissions reduction across major energy sectors. Besides being a feedstock and process gas used in many industrial processes, hydrogen is an emerging fuel alternative for transportation applications. Therefore, there is a need for increased production capacity of renewable hydrogen sources. Cryogenic electrolysis of water is currently the most mature method for generating hydrocarbon-free hydrogen and is reaching a significant scale to impact the energy landscape. However, the cost of cryogenic electrolysis of water still needs to be reduced to be economical compared to traditional sources used for hydrogen production. The availability of low-cost renewable energy sources makes lower operating costs achievable, and with material and manufacturing optimizations, there is potential for significant reductions in capital costs.

[0004] Challenges in hydrogen production using electrolyzer systems include system stability and the high cost of electrode materials. Research efforts aimed at improving the electrocatalytic activity of platinum group metal (PGM)-based catalysts are underway. Other research efforts include reducing or eliminating PGM loading by developing non-PGM electrode catalysts. What is needed is a method to reduce the electrical burden on hydrogen production and lower the cost of electrode materials while maintaining or increasing their efficiency. Brief overview of the embodiments of the present invention

[0005] This invention relates to a system for electrolyzing a solution, the system comprising: a first container in communication with at least one electrolyzer stack, the electrolyzer stack including: at least one bipolar electrode including: a bipolar plate; a porous transport layer; and a catalyst; the bipolar plate, the porous transport layer, and the catalyst being fused together as a single component; at least one separator; and a second container in communication with the at least one electrolyzer stack. In another embodiment, the system further includes a substrate. In another embodiment, the substrate supports the catalyst.

[0006] In another embodiment, the substrate comprises a conductive material. In another embodiment, the conductive material comprises iron. In another embodiment, the substrate comprises an alloy material. In another embodiment, the alloy material comprises platinum group metals. In another embodiment, the substrate comprises ceramic. In another embodiment, the bipolar plate is sintered.

[0007] The present invention also relates to a method for manufacturing a substrate, the method comprising: providing a metal powder; contacting the metal powder with a polymeric binder to form a metal-binder mixture; and sintering the metal-binder mixture. In another embodiment, the polymeric binder comprises polyvinyl alcohol. In another embodiment, the polymeric binder comprises polyethylene glycol. In another embodiment, the polymeric binder comprises carrageenan. In another embodiment, the metal powder comprises nickel. In another embodiment, the metal powder comprises titanium. In yet another embodiment, the method further comprises contacting the metal-binder mixture with a metal foam.

[0008] The present invention also relates to a substrate comprising: a sintered porous structure; a conductive material; an alloy material; and a functional gradient. In another embodiment, the porous microstructure comprises a porosity of about 20% to about 95%. In another embodiment, the substrate comprises about 2.5 g / cm³. 3 Approximately 3.4 g / cm³ 3 The density. In another embodiment, the conductive material includes iron.

[0009] The objects, advantages, and novel features of the invention, as well as its further scope of applicability, will be set forth in part in conjunction with the accompanying drawings in a detailed description, and will also be apparent in part to those skilled in the art upon examination of the following text, or may be learned by practice of the invention. The objects and advantages of the invention may be realized and obtained by the means and combinations particularly pointed out in the appended claims. Brief description of several views in the accompanying drawings

[0010] The accompanying drawings, which are incorporated in and form a part of this specification, illustrate one or more embodiments of the invention and, together with the specification, serve to explain the principles of the invention. The drawings are for illustrative purposes only and are not to be construed as limiting the invention. In the drawings:

[0011] Figure 1 This is a diagram illustrating an implementation scheme for an electrolyzer system;

[0012] Figure 2 This is a diagram illustrating an embodiment of the electrolyzer stack;

[0013] Figure 3 This is a diagram illustrating an implementation scheme for a single-cell ion exchange electrolyzer;

[0014] Figure 4 This is a diagram illustrating an embodiment of the bipolar plate;

[0015] Figure 5A This is a diagram illustrating an embodiment of an electrolyzer cell with an applied magnetic field;

[0016] Figure 5B It is shown Figure 5A The diagram shows the direction of current flow and magnetic field in the electrolyzer cell;

[0017] Figure 6A This is a diagram illustrating an embodiment of the arrangement of the photoelectrochemical system;

[0018] Figure 6B This is a diagram illustrating an embodiment of the arrangement of the photoelectrochemical system;

[0019] Figure 7 It is a process flow diagram of an implementation scheme using sputtered or electroplated electrodes;

[0020] Figure 8 This is a process flow diagram of the electrode manufacturing implementation scheme;

[0021] Figure 9 These are a series of graphs showing the initial performance and current density of the novel MEA of the present invention compared to commercially available membrane electrode assemblies (“MEAs”);

[0022] Figure 10 These are a series of graphs showing the initial performance and long-term stability of the novel MEA of the present invention compared with commercially available MEAs;

[0023] Figure 11 It is a series of diagrams illustrating the effects of selective etching and / or immersion of sacrificial material from the cathode and anode;

[0024] Figure 12 It is a series of diagrams illustrating the effects of heat treatment on the cathode and anode;

[0025] Figure 13 It is a series of photographs showing microporous structures formed by sacrificing and / or leaching material from the cathode and / or anode; and

[0026] Figure 14 This is a graph showing the long-term stability of the nitrogen-assisted electrolyzer. Invention Details

[0027] The present invention is an electrolyzer system, which may include a bipolar plate, a current collector, an insulator, an electrode containing a catalytic material and a microporous structure, and an MEA / ion exchange membrane.

[0028] The terms "one metal" or "multiple metals" are defined in the specification, claims, and drawings as compounds, mixtures, or substances containing metal atoms. The terms "one metal" or "multiple metals" include, but are not limited to, metal hydroxides, metal oxides, metal salts, elemental metals, metal ions, nonionic metals, minerals, or combinations thereof.

[0029] In the specification, claims, and drawings, the terms "catalyst" or "catalytic material" shall be used interchangeably. In the specification, claims, and drawings, the terms "isolated body" and "bipolar plate" shall be used interchangeably.

[0030] In the specification and claims, the term "leaching" is defined as a method for releasing, extracting, freeing or removing one or more metals from a material.

[0031] In the specification, claims and drawings, the term "micropore" or "microstructure" is defined as a material wherein at least a portion of the material comprises pores with a diameter of less than one millimeter.

[0032] In the specification, claims and drawings, the term "nanopore" or "nanostructure" is defined as a material wherein at least a portion of the material comprises pores with a diameter of less than one micrometer.

[0033] The terms "tank" or "vessel" are used interchangeably and are defined in the specification, claims, and drawings as any holder, compartment, container, receptacle, and / or other object capable of containing fluid. The term should cover any holder, compartment, container, receptacle, and / or other object of suitable size or material. For example, they may include large, acid-resistant tanks or containers used for commercial-scale water electrolysis.

[0034] The term "platinum group metals" includes, but is not limited to, platinum, palladium, rhodium, ruthenium, iridium, osmium, or combinations thereof.

[0035] Compared to conventional electrolyzers, this electrolyzer system can split water into hydrogen and oxygen, or nitrogen compounds into hydrogen and nitrogen, at lower voltages. It also offers higher electrode or MEA efficiency and longer-term stability compared to conventional electrolyzers.

[0036] This electrolyzer system can achieve high cell current density with reduced PGM requirements. In particular, it requires less PGM compared to conventional electrolyzers using PEM technology, and requires no PGM at all compared to conventional electrolyzers using AEM and AE technologies.

[0037] Nitrogen-assisted hydrogen production electrolyzer systems do not pose any risk of explosion due to the mixing of O2 and H2 gases because no oxygen is released. Compared to conventional water splitting systems, nitrogen-assisted hydrogen production electrolyzer systems can exhibit higher performance stability, especially during long-term operation. Replacing oxygen with nitrogen in the anodic reaction at the anode allows the electrolyzer system to operate at reduced or zero voltage and avoids anode oxidation and corrosion due to the presence of oxygen—that is, nitrogen is released instead of oxygen. Compared to electrolyzer systems that use water to produce hydrogen, nitrogen-assisted hydrogen production electrolyzer systems can have a wider stability range, for example, continuous operation for at least 100 hours with performance variations.

[0038] Now turn to the attached diagram. Figure 1 An electrolyzer system 10 is shown. A water tank 12 can supply water flow 14 to the positively charged terminal 18 of an electrolyzer stack 16. The electrolyzer stack 16 can be powered by a power source 20 connected to the positively charged terminal 18 and the negatively charged terminal 22. Electrons can flow along path 24 within the electrolyzer stack 16 to split water into oxygen and hydrogen molecules. Oxygen can exit the electrolyzer stack 16 through outlet 26, and hydrogen can exit the electrolyzer stack 16 through outlet 28. Hydrogen can be collected in a hydrogen storage tank 30.

[0039] Figure 2 An exploded view of an electrolyzer stack 16 with individual electrolyzer cells 42 is shown. Individual electrolyzer cells can be held together in the stack by connectors 32. Individual electrolyzer cells 34 may include electrodes 38 at least partially disposed between insulators and / or bipolar plates 36. A membrane 40 may be at least partially disposed between the electrodes 38. Hydrogen 27 and oxygen 25 may be prepared at the insulators and / or bipolar plates 36 and may exit the individual electrolyzer cells 34 on the opposite side.

[0040] Figure 3A single-cell ion exchange electrolyzer 42 is shown. A membrane 40 may be at least partially disposed between gaskets 52. The membrane 40 may comprise an ion exchange membrane 56, an oxygen emission reaction (“OER”) catalyst 58, and a hydrogen emission reaction (“HER”) catalyst 60. The OER catalyst 58 and the HER catalyst 60 may include a gas diffusion layer (“GDL”). The ion exchange membrane 56 may be at least partially disposed between the OER catalyst 58 and the HER catalyst 60. Gaskets 52 may be at least partially disposed between flow field plates 50. The flow field plates 50 may be at least partially disposed between an isolator and / or a bipolar plate 36. The isolator and / or the bipolar plate 36 may include an end plate 49 and a current collector 48. The single-cell ion exchange electrolyzer 42 may include an anode cell 44. The anode cell 44 may include an isolator and / or a bipolar plate 36, flow field plates 50, gaskets 52, and the OER catalyst 58. The single-cell ion exchange electrolyzer 42 may include a cathode cell 46. The cathode cell 46 may include an insulator and / or a bipolar plate 36, a flow field plate 50, a gasket 52, and a HER catalyst 60. Figure 4 An embodiment including an isolator and / or bipolar plate comprising a serpentine channel pattern 62 may be a component of a single-cell ion exchange electrolyzer 42.

[0041] Figure 5A and 5B An electrolyzer cell with an applied magnetic field 64 is shown, and a diagram illustrating the current flow and magnetic field within the electrolyzer cell with the applied magnetic field 64 is also shown. Cell assembly 65 may be at least partially disposed between a south magnetic field end 66 and a north magnetic field end 68. Cell assembly 65 may include an insulator and / or bipolar plate 36, an electrode 38, and a membrane 40. Optionally, electrode 38 may be replaced with a porous transport layer (later), and / or membrane 40 may be replaced with a MEA comprising a catalyst, a GDL, and electrode 38. Magnetic field 69 may be applied to the insulator and / or bipolar plate 36 and / or electrode 38. The magnetic field may be applied parallel to the south magnetic field end 66 and the north magnetic field end 68, and current flow may be applied perpendicular to this magnetic field. Current flow may cross and / or pass through at least one component of cell assembly 65.

[0042] Figure 6A and 6B Electrode arrangements for photoelectrochemical systems 70 and 78 are shown. Photoelectrochemical system 70 includes a photocathode 74 at least partially disposed between a photoanode 72 and a solar panel 76. Photoelectrochemical system 78 includes a photoanode 72 at least partially disposed between a photocathode 74 and a solar panel 76. The solar panel 76 can convert solar radiation into electricity and supply voltage between the photoanode 72 and / or the photocathode 74. Optionally, the photoanode 72 and / or the photocathode 74 can generate electron flow by directly receiving solar radiation.

[0043] Figure 7 An embodiment of electrode fabrication using sputtering or electroplating is illustrated. In sputtering fabrication method 80, the substrate can be pretreated by a cleaning step 82. Cleaning step 82 may include degreasing and / or deoxidation. The substrate can then undergo electrochemical activation 84 by applying an electric current. The activated substrate may undergo drying 86, followed by sputtering 88 of a compound comprising a main material and a support material. The support material may include a sacrificial material. The main material and the support material may undergo immersion 90. Optionally, the sacrificial compound may undergo doping 92 to introduce a dopant into the main material. The substrate having the sacrificial compound may undergo heat treatment 94.

[0044] In electroplating method 96, the substrate may be pretreated by a cleaning step 82. Cleaning step 82 may include degreasing and / or deoxidation. The substrate may then undergo electrochemical activation 84 by applying an electric current. The activated substrate may undergo electroplating 98 with a compound comprising a main material and a support material. The support material may include a sacrificial material. The main material and support material may undergo immersion 90. Optionally, the sacrificial compound may undergo doping 92 to introduce a dopant into the main material. The substrate containing the sacrificial compound may undergo heat treatment 94.

[0045] Figure 8 An electrode manufacturing method 100 is illustrated. The electrode substrate may undergo chemical and electrochemical pretreatment 102, followed by a first material deposition 104. The substrate may then undergo a first heat treatment 106, followed by a first reagent cleaning 108 and a second reagent cleaning 110. Water may include distilled water and / or purified water. The substrate may then undergo acid cleaning 122, followed by a third reagent cleaning 114. The substrate may then undergo electrochemical activation 116, followed by a fourth reagent cleaning 118. The substrate may then undergo drying 120 and undergo a second material deposition 122. The substrate with the deposited material may then undergo selective etching and / or immersion 124, followed by a fifth reagent cleaning 126 and a second heat treatment 128. Reagents in any cleaning step may include isopropanol, distilled water, purified water, acetone, ethanol, or combinations thereof.

[0046] Figure 9 A series of graphs comparing the initial performance and stability data of commercially available MEAs with those of the present invention are shown. The results demonstrate that the MEA of the present invention can achieve the same current density at a smaller applied voltage compared to commercially available MEAs. The results also demonstrate that the MEA of the present invention exhibits improved long-term stability compared to commercially available MEAs.

[0047] Figure 10A series of figures are shown illustrating the initial performance and current density of the novel electrode of the present invention compared to commercially available electrodes. The figures compare the initial performance and stability data of a commercially available MEA incorporating a cation exchange membrane with that of the MEA of the present invention incorporating a cation exchange membrane. The cation exchange membrane is at least partially disposed between the anode and cathode compartments of both the commercially available MEA and the MEA of the present invention.

[0048] Figure 11 The effects of selective etching and / or immersion of sacrificial material from the cathode and anode are illustrated. These figures show the performance of the cathode with and without selective etching or immersion. For a given voltage, the cathode with selective etching or immersion retains more energy compared to the cathode without selective etching or immersion. These figures also show the performance of the anode with and without selective etching or immersion. For a given voltage, the anode with selective etching or immersion retains more energy compared to the anode without selective etching or immersion.

[0049] Figure 12 The effects of heat treatment on the cathode and anode are shown. These figures illustrate the performance of the cathode and anode with and without heat treatment. Heat treatment improves the performance of both the cathode and anode.

[0050] Figure 13 The microporous structure formed by sacrificing and / or leaching material from the cathode and / or anode is shown. Image series 130 shows pores 134 dispersed between the sacrificial and / or leached material 132. Image series 130 also shows catalytic material 138 bonded to a substrate 136.

[0051] Figure 14 The results show that in 1M KOH and 0.2M N2H4, at a current density of 10 mA•cm -2 The dual-electrode hydrazine electrolyzer demonstrated long-term stability after 100 hours. The voltage remained stable after 100 hours. During operation of the hydrazine electrolyzer system, the voltage remained at approximately 0.45 V.

[0052] An electrolyzer system may include at least one electrolyzer stack. The electrolyzer stack may include at least one electrolytic cell. The electrolytic cell may include an anode cell and / or a cathode cell. The anode and / or cathode cells may include a bipolar plate, a flow field plate, gaskets, electrodes, a catalyst, or a combination thereof. A membrane may be disposed between the anode cell and the cathode cell. The bipolar plate may include end plates, current collectors, flow channels, or a combination thereof, and may facilitate the conversion of dissolved gases in the solution into gaseous phases. The flow field plate may include a flow field.

[0053] The electrolyzer system may include membranes. Membranes may include proton exchange membranes (“PEM”), anion exchange membranes (“AEM”), alkaline electrolyzer (“AE”) stacks, or combinations thereof. PEM and / or AEM may include PGM. PEM and AEM may be ion exchange membranes. The electrolyzer system may further include cation exchange membranes, including but not limited to Nafion 115, Nafion 117, Nafion 212, perfluorosulfonic acid membranes, polytetrafluoroethylene membranes, chlor-alkali membranes, carboxylic acid membranes, or combinations thereof. The electrolyzer may achieve high cell current densities using electrodes comprising metal or mixed metal-metal oxide microstructures and / or nanostructures. The electrolyzer may include cathode catalysts and / or anode catalysts. Cathode catalysts and / or anode catalysts may include PGM. A magnetic field may be applied externally to the electrolyzer system, which includes, but is not limited to, PEM, AEM, AE stacks, electrodes, catalysts, or combinations thereof. The electrolyzer system may be a hydrogen electrolyzer system. The membrane may contain at least about 0.2 mg·cm⁻¹. -2 Approximately 0.2 mg·cm -2 Approximately 3 mg·cm -2 Approximately 0.4 mg·cm -2 Approximately 2.5 mg·cm -2 Approximately 0.6 mg·cm -2 Approximately 2.0 mg·cm -2 Approximately 0.8 mg·cm -2 Approximately 1.5 mg·cm -2 Approximately 1.0 mg·cm -2 Approximately 1.2 mg·cm -2 or approximately 3 mg·cm -2 .

[0054] The MEA may include an AEM. The MEA may include an adhesive. The adhesive may include anionic adhesives, cationic adhesives, or ionomer adhesives, or combinations thereof. The adhesive may be at least partially disposed between the anode and the AEM. The adhesive may also be at least partially disposed between the cathode and the AEM. The AEM may include anion exchange membranes and / or cation exchange membranes. The adhesive may increase the ionic conductivity between the AEM and the anode and / or cathode by at least about 10%, about 10% to about 40%, about 15% to about 35%, about 20% to about 30%, or about 40%. The adhesive may include ionomers and may include anionic or cationic properties. The adhesive may be at least partially disposed between the AEM and the corresponding anode or cathode in one of the following orders:

[0055] Anode, first (anionic) binder, AEM, second (anionic) binder, cathode;

[0056] Anode, first (cationic) binder, AEM, second (cationic) binder, cathode;

[0057] Anode, first (anionic) binder, AEM, second (cationic) binder, cathode; or

[0058] Anode, first (cationic) binder, AEM, second (anionic) binder, cathode.

[0059] The membrane of a MEA can include PEM. The current density of PEM can be less than about 4 A•cm. -2 Approximately 0.5 A•cm -2 Approximately 4 A•cm -2 Approximately 1 A•cm -2 Approximately 3.5 A•cm -2 Approximately 1.5 A•cm -2 Approximately 3 A•cm -2 Approximately 2 A•cm -2 To approximately 2.5 A•cm -2 or approximately 4 A•cm -2 The cationic binder can be at least partially disposed between the anode and the PEM, and / or between the cathode and the PEM. The cationic binder may contain ionomers and can be prepared from an ionomer solution of at least about 5%, about 5% to about 20%, about 10% to about 15%, or about 20% by weight of the ionomer. In conventional PEM electrolyzer technology, the anode and cathode catalysts comprise PGMs. Platinum is primarily used to manufacture the cathode, while iridium and ruthenium are used to manufacture the anode. The amount of platinum group materials used in conventional PEM electrolyzer technology is typically between 1 and 3 mg / cm³. 2 Between. The electrolyzer system of the present invention, which includes PEM, may include electrodes containing at least about 0.01 mg / cm³. 2 Approximately 0.01 mg / cm 2 Approximately 0.1 mg / cm 2 Approximately 0.02 mg / cm 2 To approximately 0.09 mg / cm 2 Approximately 0.03 mg / cm 2 Approximately 0.08 mg / cm³ 2 Approximately 0.04 mg / cm 2 Approximately 0.07 mg / cm³ 2 Approximately 0.05 mg / cm 2 Approximately 0.06 mg / cm³ 2 Approximately 0.1 mg / cm 2 PEMs can be used without sacrificing performance. PEMs may also include cation exchange membranes and / or cation-exchange membranes.

[0060] Electrolyzer systems can include photoelectrochemical (“PEC”) systems for water splitting. PEC systems can include transparent / semi-transparent photoanodes (PA), transparent / semi-transparent photocathodes (PC), solar cells (SC), or combinations thereof. Compared to the amount of hydrogen produced by solar panels and electrolyzers without a PEC system, PEC systems can allow the production of green hydrogen from sunlight and water with high solar-to-hydrogen efficiency, i.e., high hydrogen yield. PEC systems can incorporate non-IIIV compound materials, such as conductive metal oxides and perovskite materials.

[0061] Electrolyzer systems can include solar panels as a power source. These solar panels can be integrated into the PEC system to directly produce green hydrogen from sunlight and water with increased solar-to-hydrogen (STH) efficiency.

[0062] The photoanode may include n-type semiconductors and / or perovskite materials, including but not limited to BiVO4, TiO2, WO3, SrTiO3, Fe2O3, ZnO, or combinations thereof. The n-type semiconductors and / or perovskite materials are used to form a heterostructure with a band gap, and may be transparent. Other compatible materials may also be deposited simultaneously during anode material deposition to form a high-performance n-type semiconductor. ZnO and Ti, or ZnO, Ti, and W, may be deposited simultaneously to form a high-performance mixed oxide. The photoanode may also be coated with nanoparticles of an anode catalyst, including but not limited to PGM-based or Ni-based alloys, to improve the overall performance of the photoanode.

[0063] The photocathode may include p-type semiconductors and / or perovskite materials, including but not limited to alloys or combinations thereof based on copper-based oxides, p-type metal oxides. The p-type semiconductors and / or perovskite materials may form heterostructures with band gaps, and may be transparent. The photocathode may be coated with nanoparticles of a cathode catalyst, including but not limited to PGM-based or Ni-based alloys, to improve the overall performance of the photocathode.

[0064] Photoelectrodes, such as photoanodes and / or photocathodes, can be fabricated to achieve an ampere- ... -2 The photocurrent density is such that the fill factor is greater than 50%. The materials in the photoelectrode can be optimized to achieve a crystalline structure. This crystalline structure may require the formation of nanocrystals on the photoelectrode. Nanocrystals can be formed by adjusting the deposition of materials onto the electrode, for example, by controlling the deposition time, deposition temperature, deposition pressure, controlling the reactive gas, or combinations thereof. The interface between the nanocrystals and the electrode surface can also be optimized to integrate the nanocrystals into the photoelectrode. The interface can be optimized by controlling the deposition parameters of each material, for example, by controlling the deposition time, deposition temperature, deposition pressure, controlling the reactive gas, deposition power, gas flow rate, or combinations thereof. Interface engineering can prevent changes in the surface morphology and shape of the nanocrystals.

[0065] The photoanode and photocathode can then be integrated together using sequential deposition. The integrated photoelectrode can be directly integrated with the solar cell or solar panel using physical and / or chemical deposition. Integration of the photoelectrode with the solar cell or solar panel can be achieved by controlling the light absorption of each photoelectrode or solar component without interfering with the performance of the remaining photoelectrodes or solar components. Light absorption can be controlled by adjusting the crystal quality and thickness of the material through the modification of deposition parameters.

[0066] The STH efficiency of a PEC system depends on the short-circuit photocurrent density, the Faraday efficiency of hydrogen emission, and the incident illumination power density. All of these parameters must be measured under standard sunlight illumination conditions (AM 1.5 G solar spectrum). The STH efficiency can be measured according to Equation 1.

[0067] (1)

[0068] By using the thermodynamic potential (V) redox The STH efficiency is calculated by multiplying the electrolysis current (IWE) and the Faraday efficiency (ηF) for hydrogen emission by two, and then dividing by the input optical power (Pin).

[0069] PEC systems can use non-III-V materials that can influence photocurrent density and hydrogen emission, while achieving STH efficiencies up to 30%. This 30% STH efficiency is approximately three times that achieved using conventional PEC technology.

[0070] An electrolyzer system may include at least one electrolytic cell at least partially disposed between a pair of electromagnetic plates. The pair of electromagnetic plates may be arranged such that current flows within a stack electromagnetically perpendicular to the electrolytic cell. The electromagnetic plates may generate a quasi-uniform magnetic field. The electromagnetic plates may accelerate hydrogen collection. Hydrogen acceleration may be achieved through the synergistic effect of the quasi-uniform magnetic field and the current flow of charge carriers with the electrolyzer stack. Charge carriers may include protons.

[0071] Electrolyzer systems can produce hydrogen from nitrogen compounds in solution (nitrogen-assisted hydrogen production). Nitrogen-assisted hydrogen production can occur in membrane electrolyzers (PEM or AEM), alkaline electrolyzers including separators to separate N2 and H2 gases, membrane-free electrolyzers, or combinations thereof. Nitrogen-assisted hydrogen production may require contacting the nitrogen compounds with the electrolyzer. Nitrogen and hydrogen can be produced according to Equation 2 or 5, which originates from the anodic half-reactions of Equations 3 and 6, and the cathodic half-reactions of Equations 4 and 7.

[0072] N2H4 → N2 + 2H2 E VS.SHE = -0.33 V(2)

[0073] Anode: N₂H₄ + 4OH⁻ - → N2 + 4H2O + 4e - E VS.SHE = -1.16 V(3)

[0074] Cathode: 4H₂O + 4e⁻ - → 2H2 + 4OH - E VS.SHE = -0.83 V(4)

[0075] CO(NH2)2 + H2O → 3H2 + N2 + CO2 E VS.SHE = +0.37 V(5)

[0076] Anode: CO(NH2)2 + 6OH - → N2 + CO2 + 5H2O + 6e - E VS.SHE = -0.46 V(6)

[0077] Cathode: 6H₂O + 6e - → 3H2 + 6OH - E VS.SHE = -0.83 V(7)

[0078] Nitrogen compounds can include hydrazine, urea, and any other reagent that can decompose into nitrogen upon dissolution in an electrolyte. Nitrogen-assisted hydrogen production can release nitrogen, rather than oxygen, at the anodic site (e.g., the anode). Nitrogen release can reduce the total cell voltage and power required to operate the electrolyzer system. The surface properties of the electrodes in the electrolyzer system can be tuned to shift the electrode electrochemical potential. Electrolyzer systems that break down nitrogen compounds to release nitrogen and oxygen can be operated at applied voltages of at least about 10 mV to about 1.5 V, about 50 mV to about 1.0 V, about 100 mV to about 0.8 V, about 0.2 V to about 0.6 V, or about 1.5 V. Electrolyzer systems employing nitrogen-assisted hydrogen production can operate without any applied voltage and / or generate electricity as a byproduct.

[0079] An electrolyzer system for nitrogen-assisted hydrogen production may include: an electrolyte bath, including but not limited to hydrazine, urea, any other reagent or combination thereof that can decompose into nitrogen upon dissolution in the electrolyte; distilled water; an alkali metal electrolyte, including but not limited to KOH, NaOH, K₂CO₃ or combinations thereof; an acidic electrolyte, including but not limited to H₂SO₄, H₂CO₃ or combinations thereof; or combinations thereof. KOH may be present at a concentration of at least about 1.0 M, about 1.0 M to about 5.0 M, about 1.5 M to about 4.5 M, about 2.0 M to about 4.0 M, about 2.5 M to about 3.5 M, or about 5.0 M. Hydrazine, urea, any other reagent or combination thereof that can decompose into nitrogen upon dissolution in the electrolyte may be present at a concentration of at least about 0.01 M, about 0.01 M to about 3.0 M, about 0.5 M to about 2.5 M, about 1.0 M to about 2.0 M, or about 3.0 M of N₂H₄ or CO(NH₂)₂. The bath can be operated at temperatures ranging from at least about 20°C, from about 20°C to about 80°C, from about 25°C to about 75°C, from about 30°C to about 70°C, from about 35°C to about 65°C, from about 40°C to about 60°C, from about 45°C to about 55°C, or about 80°C. By controlling the concentration of nitrogen compounds through a closed-loop circulating bath and an automatic dosing system, nitrogen emission reactions are made dominant, preventing oxygen emission reactions. The risk of explosion caused by mixtures of H2 and O2 is eliminated.

[0080] The electrolyzer system may include a power source. The power source may generate alternating current, direct current, pulsed current, or a combination thereof. The power source may generate electrical energy from renewable energy sources, including but not limited to solar radiation, thermal energy, tidal current, wind energy, bioenergy, or combinations thereof. The power source may transmit electrical energy, such as current, to the electrolyzer cells of the electrolyzer system. Electrical energy may be transmitted from the power source to the electrolyzer system via at least one wire.

[0081] The electrolyzer system can operate at temperatures of at least about 20°C, about 20°C to about 80°C, about 30°C to about 70°C, about 40°C to about 60°C, and about 80°C. The operating temperature is preferably about 60°C.

[0082] The electrolyzer system may include an electrolyte. The electrolyte may include an alkaline electrolyte. The alkaline electrolyte may contain an alkali metal, including but not limited to lithium (“Li”), sodium (“Na”), potassium (“K”), rubidium (“Rb”), cesium (“Cs”), francium (“Fr”), or combinations thereof. The electrolyte may include, but is not limited to, KOH, K₂CO₃, NaOH, or combinations thereof. The concentration of the electrolyte may be at least about 0.1 M, about 0.1 M to about 3 M, about 0.5 M to about 2.5 M, about 1.0 M to about 2.0 M, or about 3.0 M.

[0083] MEAs can be directly bonded to electrodes and / or at least partially disposed between a pair of electrodes. The pair of electrodes can comprise an anode and a cathode. The anode and cathode can comprise a gas-derived polymer (GDL) and a catalyst in communication with the GDL. The catalyst can be attached to the GDL by physical or chemical deposition. The GDL can comprise a porous layer. Optionally, the anode and / or cathode can be GDLs having a catalyst coated on the surfaces of the anode and / or cathode. The GDL can comprise conductive fibers, paper, foam, mesh, felt, or combinations thereof. The GDL can comprise a thickness of at least about 0.1 mm, about 0.1 mm to about 2 mm, about 0.2 mm to about 1.6 mm, about 0.4 mm to about 1.2 mm, about 0.6 mm to about 0.8 mm, or about 2 mm. The GDL can comprise a specific porosity or variable porosity of at least about 10%, about 10% to about 99%, about 20% to about 97%, about 30% to about 95%, about 40% to about 90%, about 50% to about 80%, about 60% to about 70%, or about 99%.

[0084] Electrodes (e.g., cathodes and / or anodes) and catalysts can be selected from HER and / or OER volcano graphs and can depend on the desired current density of the electrolyzer system. HER catalysts can include, but are not limited to, Mo, Nb, W, Co, Ni, Re, Rh, Pd, Pt, Ir, Au, Ag, Fe, Ti, Ta, Tl, Cu, Bi, Cd, Ga, or combinations thereof. OER catalysts can include, but are not limited to, Cr, Ru, Mn, Fe, Ir, Co, Rh, Ni, Pt, Cu, Pt, Ag, Zn, Au, NbOx, ReOx, VOx, CrOx, SnObx, MoOx, MnOx, PtOx, IrOx, RuOx, TiOx, NiOx, PbObx, CoOx, or combinations thereof. HER and / or OER can allow the electrolyzer system, electrolytic cell, and / or electrodes to operate at a cell voltage of 1.8 V at a current density of at least about 0.5 A•cm. -2 Approximately 0.5 A•cm -2 Approximately 2A•cm -2 Approximately 0.75 A•cm -2 To approximately 1.75 A•cm -2 Approximately 1 A•cm -2 To approximately 1.5 A•cm -2 Or approximately 2 A•cm -2 Operating at current densities. The cathode and anode catalysts may contain non-PGM components selected from one of the following:

[0085] • (Ni 0.7±0.1 Fe 0.3±0.1 ) α X β Y γ, where α+β+γ=100% (α≥50%, β and γ make up the remaining 50%, each range is 0-50%), X and Y are selected from one of the following: Cr, Co, Mo, W, O, S, P, N;

[0086] • (Al 0.5±0.1 (Ni) 0.7±0.1 Fe 0.3±0.1 ) α X β Y γ ) 0.5±0.1 Where α+β+γ=100% (α≥50%, β and γ constitute the remaining 50%, each ranging from 0-50%), X and Y are selected from one of the following: Cr, Co, Mo, W, O, S, P, N, and wherein the catalyst is activated by leaching aluminum to form a porous structure; and

[0087] • (Al 0.5±0.1 (Ni) 0.7±0.1 Mo 0.3±0.1 ) 0.5±0.1 The catalyst is activated by leaching aluminum to form a porous structure, and the current density is greater than 2 A*cm at a cell voltage of 1.8 V. -2 .

[0088] The cathode catalyst may contain PGM selected from the following:

[0089] • (Al 0.5±0.1 (Mo) 0.7±0.1 Pt 0.3±0.1 ) 0.5±0.1 ;and

[0090] • Al 0.7±0.1 Pt 0.3±0.1。

[0091] The anode catalyst may comprise a PGM selected from the following that has been activated by leaching aluminum to form a porous structure:

[0092] • (Al 0.5±0.1 ) (Ir x Ru y ) 0.5±0.1 ;

[0093] • (Ni 0.7±0.1 Fe 0.3±0.1 ) α X β Y γ The inner layer, wherein α + β + γ = 100% (α ≥ 50%, β and γ constitute the remaining 50%, each ranging from 0 to 50%), X and Y are selected from one of the following: Cr, Co, Mo, W, O, S, P, N, and Al.0.7±0.1 (IrOx) 0.3±0.1 The outer layer;

[0094] • (Ni 0.7±0.1 Fe 0.3±0.1 ) α X β Y γ The inner layer, wherein α + β + γ = 100% (α ≥ 50%, β and γ constitute the remaining 50%, each ranging from 0 to 50%), X and Y are selected from one of the following: Cr, Co, Mo, W, O, S, P, N, and (Al). 0.5±0.1 (Ir) x Ru y ) 0.5±0.1 The outer layer; and

[0095] • (Ni 0.7±0.1 Fe 0.3±0.1 ) α Al β (where α+β+γ=100% (α≥50%, β and γ make up the remaining 50%, each in the range of 0-50).

[0096] The bipolar plate may include gas and / or liquid flow channels. These channels may include passages. Passages may include, but are not limited to, serpentine, column-pin, or parallel or straight channel patterns, or combinations thereof. The bipolar plate may include current collectors, electrolyte pressure and flow controllers, resistance regulators, or combinations thereof. The channel pattern of the bipolar plate and the surface engineering of the material deposited on these plates can affect electrolyte pressure, electrolyte flow, and / or the resistance of the bipolar plate. The channel pattern of the bipolar plate may include defined depth, width, and curvature.

[0097] The channel pattern of the bipolar plate can facilitate liquid and / or gas management within the electrolyzer. Optimizing the bipolar plate can prevent gas trapping within the electrolyzer system and can lead to improved electrolyte flow and gas release from the electrolyzer system. Optimization of the bipolar plate can be accomplished by altering the pattern of the gas and / or liquid flow channels to prevent gas trapping within the bipolar plate and / or electrolyzer system, and by coating the bipolar plate with conductive and / or corrosion-resistant materials to prevent oxidation and promote conductivity. The bipolar plate may include nickel, stainless steel, titanium, carbon-based products, and aluminum, plastics, acrylics, foams, or combinations thereof. The conductive and corrosion-resistant materials may include alloys, including but not limited to gold, silver, copper, aluminum, nickel, iron, molybdenum, chromium, niobium, ruthenium, rhodium, palladium, osmium, iridium, platinum, zinc, bronze, brass, or combinations thereof.

[0098] The electrolyzer system may include electrodes manufactured by sputtering or electroplating methods. Electrodes may be manufactured by first pretreating the substrate. The substrate may include, but is not limited to, nickel, ferrochrome, molybdenum, copper, titanium, steel, stainless steel, nickel-chromium alloys, nickel-iron alloys, nickel-molybdenum alloys, nickel-copper alloys, titanium alloys, felt, paper, foam, or combinations thereof. The substrate may be cleaned and / or degreased to remove oil, grease, and / or native oxides. Cleaning and / or degreasing may be performed by ultrasonic cleaning (resistivity > 18 Ω x cm) and / or contact with NaOH, acetone, ethanol, methanol, isopropanol, distilled water, or combinations thereof. The substrate may be cleaned and / or degreased at least once, for at least about 5 min, about 5 min to about 30 min, about 10 min to about 25 min, about 15 min to about 20 min, or about 30 min. Native oxides may be removed from the surface of the substrate by contacting it with an acid. The substrate may be immersed in an acidic solution. The acid may include, but is not limited to, hydrochloric acid, hydrofluoric acid, sulfuric acid, or combinations thereof.

[0099] Optionally, the substrate can be contacted with an etchant that can at least partially remove the native oxide from the substrate. The concentration of the acid in the solution can be at least about 5%, about 5% to about 50%, about 10% to about 45%, about 15% to about 40%, about 20% to about 35%, or about 25% to about 30% by weight (w / w). The acid can be at a temperature of at least about 50°C, about 50°C to about 80°C, about 55°C to about 75°C, about 60°C to about 70°C, or about 80°C.

[0100] The substrate can be electrochemically activated by applying an electric current. The applied current density can be at least about 40 mA / cm². 2 Approximately 40 mA / cm 2 Approximately 1000 mA / cm 2 Approximately 80 mA / cm 2 Approximately 900 mA / cm 2 Approximately 100 mA / cm 2 Approximately 800 mA / cm 2 Approximately 200 mA / cm 2 Approximately 700 mA / cm 2 Approximately 300 mA / cm 2 Approximately 600 mA / cm 2 Approximately 400 mA / cm 2 Approximately 500 mA / cm 2 or approximately 1000 mA / cm 2 The substrate can be activated by immersion in HCl followed by washing and / or rinsing with acetone and / or deionized water.

[0101] Powder metallurgy (“PM”) technology can be used to produce substrates for electrodes used in electrolyzer stacks. The substrate can be a platform on which a catalyst is coated. The substrate can be a conductive material, including but not limited to iron-containing metals, alloys, or combinations thereof. The substrate can be conductive and includes conductive metals, including but not limited to nickel, titanium, stainless steel, or combinations thereof. The substrate can operate in the chemical environment generated in the electrolyzer stack. The substrate can include, but is not limited to, nickel, iron, molybdenum, cobalt, titanium, tantalum, graphite, aluminum, tungsten, copper, silver, gold, platinum group metals, or combinations thereof. Alloying metals may also be present to customize the properties of the substrate. Alloying metals can include, but are not limited to, zinc, tin, lead, or combinations thereof. The substrate can contain ceramic components, transition metal oxides, catalytically active materials, or combinations thereof. Catalytically active materials can include, but are not limited to, iridium, platinum, molybdenum, titanium, tungsten, cobalt, nickel, niobium, palladium, ruthenium, rhenium, tantalum, bismuth, strontium, lanthanum, vanadium, indium, gold, silver, iron, copper, magnesium, zinc, chromium, nitrides or oxides, phosphides, and sulfides of the above materials, or combinations thereof. Any combination of catalytically active materials can contribute to the catalytic process.

[0102] Ceramic and / or metal powders can be combined by mixing or grinding the precursor powders together in a dry or wet state. In the dry state, the powders can be blended with solid lubricants and binders. In the wet state, binders, lubricants, plasticizers, surfactants, or combinations thereof can be combined with a suitable carrier fluid having a solids loading of up to 60 vol%. The carrier fluid can include, but is not limited to, alcohols, ethanol, water, acetone, or combinations thereof. The carrier fluid may include at least about 10 vol%, about 10 vol% to about 75 vol%, about 20 vol% to about 60 vol%, about 30 vol% to about 50 vol%, or about 75 vol% of solids loading. The viscosity of the slurry can be at least about 50 mPa·s, about 50 mPa·s to about 4500 mPa·s, about 100 mPa·s to about 4250 mPa·s, about 150 mPa·s to about 4000 mPa·s, about 200 mPa·s to about 3750 mPa·s, about 300 mPa·s to about 3500 mPa·s, about 400 mPa·s to about 3250 mPa·s, about 500 mPa·s to about 3000 mPa·s, about 750 mPa·s to about 2500 mPa·s, about 1000 mPa·s to about 2250 mPa·s, about 1000 mPa·s to about 2000 mPa·s, about 1250 mPa·s to about 1750 mPa·s, or about 4500 mPa·s. The viscosity can depend on the manufacturing technique. Mechanical alloying can also be used to produce alloy materials by mechanically combining the aforementioned metals. Other manufacturing techniques may include, but are not limited to, spray drying, freeze drying, powder tumbling, spheroidizing methods, sieving, screen cutting, or combinations thereof. Following these manufacturing techniques, the material can be compacted into "green" powder particles. Additional manufacturing techniques may include, but are not limited to, gel casting, tape casting, extrusion, or combinations thereof, of the substrate material.

[0103] The fabrication of the substrate may include powder compaction, wherein the compressed sheet may include a thickness of at least about 75 µm, about 75 µm to about 2500 µm, about 100 µm to about 2000 µm, about 200 µm to about 1800 µm, about 400 µm to about 1600 µm, about 600 µm to about 1400 µm, about 800 µm to about 1200 µm, or about 2500 µm. The compressed sheet may include pressed and / or compacted powder aggregates bonded together by a polymer matrix. The compressed sheet having pressed and / or compacted powder agglomerates forms green powder particles. The green powder particles can then be sintered by subjecting the green powder particles to a binder burn-off step, followed by partial sintering to retain the porous structure left by the incomplete compaction process and the burn-off polymer binder. Another method may use the extrusion or casting of a slurry to produce a tape or film, which is then subjected to a binder burn-off and sintering process. The thickness of the tape or film used in this method can be at least about 1 µm, about 1 µm to about 2000 µm, about 10 µm to about 1800 µm, about 50 µm to about 1600 µm, about 75 µm to about 1400 µm, about 100 µm to about 1200 µm, about 200 µm to about 1000 µm, about 300 µm to about 800 µm, about 400 µm to about 700 µm, about 500 µm to about 600 µm, or about 2000 µm. The tape or film can be single-layered or multi-layered.

[0104] The sintering process can be carried out under vacuum or in the presence of an inert gas, including but not limited to argon, helium, or combinations thereof. The sintering process can also be carried out in the presence of other gases, including but not limited to nitrogen, methane, hydrogen, sulfur-containing gases such as H2S and SO2, or combinations thereof. The sintering process can generate desired microstructures and functional gradients within the PM substrate to form a sintered porous structure. A functional gradient is a region spanning variations in material properties across the material and can include variations in density and composition across the depth of the substrate material, but typically both. Sintering and PM fabrication can produce highly porous regions. Highly porous regions can include porosities of at least about 20%, about 20% to about 95%, about 25% to about 90%, about 30% to about 85%, about 35% to about 80%, about 40% to about 75%, about 45% to about 70%, about 50% to about 65%, and about 55% to about 60%. Porous regions can serve as substrates for catalysts.

[0105] The contact resistance between the bipolar plate, the porous transport layer (“PTL”), and the catalyst determines the performance of the electrolyzer stack. An integrated single unit of the “bipolar electrode” can be created by fusing the bipolar plate, PTL, and catalyst together to form a single component that eliminates the contact resistivity between parts of the electrolyzer stack. The bipolar plate can improve the efficiency and long-term stability of the electrolyzer stack. Compared to current technologies used in anion exchange membrane electrolyzers or fuel cells and proton exchange membrane electrolyzers or fuel cells, there is a mechanical connection between the porous transport layer and the bipolar plate. Moreover, the catalyst particles are loosely connected to each other by ionomers, resulting in high contact resistance and extremely low catalyst utilization due to the deactivation of some parts of the catalyst.

[0106] Bipolar plates can increase the mechanical contact between components of an electrolyzer stack and can increase the mass transfer, activation, and ohmic resistance of the electrolyzer stack. Increased mechanical contact can lead to enhanced overpotential and prevent a decline in long-term stability by eliminating contact resistance. In our proposed technique, the bipolar plates and electrodes can be sintered together at high temperatures, ranging from at least about 500°C, about 500°C to about 1100°C, about 600°C to about 1000°C, about 700°C to about 900°C, or about 1100°C. Sintering can be performed in the presence of a gas, including but not limited to argon, nitrogen, hydrogen, oxygen, sulfur, phosphides, or combinations thereof. Sintering can also be performed under vacuum or in the presence of ambient air. Sintering the bipolar plates allows the porous transport layer and catalyst to operate with improved efficiency. Sintering the bipolar plates allows the porous transport layer and electrodes and / or catalyst to be fused together as a single component and operated as a single electrolyzer workpiece.

[0107] Sputtering or electrodeposition can be used to apply materials to a substrate. If sputtering is used to apply the material, the substrate can undergo drying. Drying can include nitrogen drying. Optionally, drying can be performed in a vacuum oven at a temperature range of at least about 60°C, about 60°C to about 250°C, about 80°C to about 230°C, about 100°C to about 210°C, about 120°C to about 190°C, about 130°C to about 170°C, or about 250°C. The substrate can be completely dried. If electroplating is used to apply the material, the substrate can be rinsed with a solvent. The solvent can include distilled water and / or purified water.

[0108] Materials can be deposited onto the surface of an electrode substrate. These materials may include compound materials. Compound materials can be deposited onto the surface of the substrate through physical deposition, including but not limited to sputtering, electron beam evaporation, or combinations thereof; or chemical deposition, including but not limited to electroplating, electrochemical deposition, or combinations thereof. The compound material may include a base material and a support material. The base material may include a catalyst. The catalyst may include, but is not limited to, Ir, Pt, Ru, Re, Pd, Ni, Fe, Mo, Cr, W, Ti, Co; alloys of Ir, Pt, Ru, Re, Pd, Ni, Fe, Mo, Cr, W, Ti, Co; or combinations thereof. The compound material may include, but is not limited to, NiPt, NiIr, NiRu, PtIr, PtRu, IrRu, IrW, IrTi, IrPd, or combinations thereof. The support material may include sacrificial materials and dopants.

[0109] The sacrificial material may include, but is not limited to, Li, Ca, Na, Al, Mg, Zn, or combinations thereof. Compared to the primary catalyst, the sacrificial material may include a lower electrochemical potential. The primary and supporting materials can be simultaneously deposited onto the substrate. The amount of primary and supporting materials deposited onto the substrate may be at least 25% of the substrate weight. The sacrificial material can subsequently be leached from the compound material by selective etching. The sacrificial material can be selectively etched and / or leached using an etchant or etching method. Negligible etching and / or etching of the primary material may occur during the leaching and / or selective etching processes. The primary and sacrificial materials can be simultaneously deposited using physical and / or chemical deposition methods.

[0110] When using physical deposition methods, the primary and sacrificial materials can be deposited simultaneously using composite targets and / or composite target precursors, or multiple targets and / or multiple target precursors. The compounds and / or multiple targets can vary depending on the physical deposition method. Precursors can be atoms in the compounds and / or multiple targets, such as Pt, Ni, etc. Choosing an appropriate target or precursor allows for the deposition, i.e., bonding, of the compound material to the substrate. For example, if the compound material is deposited by sputtering, a sputtering target can be used. A sputtering target can be a single material, including but not limited to Pt, Ni, or combinations thereof, and / or combinations of materials, including but not limited to NiPt, NiMo, NiPtIr, or combinations thereof. The target or compound target can be specifically designed for this method. For example, if electron beam evaporation is used to deposit the compound material onto the substrate, a precursor can be used instead of a compound or multiple target. Mixed salt compounds or salts of compound materials can be used to coat the compound material onto the substrate using chemical deposition methods. Salts may include, but are not limited to, NiCl₂∙6H₂O, FeCl₂∙4H₂O, CoCl₂∙6H₂O, (NH₄)₂MoO₄, ZnCl₂, T / H₂PtCl₆, CoCl₂∙6H₂O, Ti / IrCl₄∙H₂O, ZnCl₂, or combinations thereof. When coating compound materials using electrochemical deposition, pulsed current waves can be used. For t on The range of the pulse wave can be at least about 50. S, approximately 50 S to approximately 5000 S, approximately 100 S to approximately 4500 S, approximately 200 S to approximately 4000 S, approximately 300 S to approximately 3500 S, approximately 400 S to approximately 3000 S, approximately 500 S to approximately 2500 S, approximately 600 S to approximately 2000 S, approximately 700 S to approximately 1500 S, approximately 800 S to approximately 1000 S, or approximately 5000 S. For t off The range of the pulse wave can also be at least about 10. S, approximately 10 S to approximately 1000 S, approximately 100 S to approximately 900 S, approximately 200 S to approximately 800 S, approximately 300 S to approximately 700 S, approximately 400 S to approximately 600 S or approximately 1000 S. Individual compound materials can be deposited individually and simultaneously to achieve the target composition, i.e., the main material and support material can be co-deposited onto the substrate simultaneously. Simultaneous deposition allows for the formation of alloys and electrodes using ten times less PGM family materials, while exhibiting a higher degree of catalytic activity compared to conventional electrodes. The catalytic activity of the electrode involves the surface of the active region. Immersion and / or selective etching of the sacrificial material results in the formation of microporous and / or nanoporous structures within the electrode. The immersion and / or selective etching of the sacrificial material leaves pores within the compound material. The formation of microporous and / or nanoporous structures increases the exposed surface area of ​​the catalyst material and / or the active region. The increased surface area increases the catalytic activity of the electrode while reducing the amount of catalyst material required to fabricate the electrode. The active region can be increased by at least about 30%, about 30% to about 150%, about 40% to about 125%, about 50% to about 100%, about 60% to about 75%, or about 150%. The surface area of ​​the catalyst can be increased by at least about 10%, about 10% to about 75%, about 20% to about 70%, about 30% to about 60%, about 40% to about 50%, or about 75%.

[0111] Dipping and / or selectively etching sacrificial materials can form micropores and / or nanopores in compound materials. Porous compound materials can form microporous and / or nanoporous structures for electrodes. The pore size in the nanopore structure can be approximately the width of the atoms being dipped and / or selectively etched, such that the pore size is wide enough to receive the dipped and / or selectively etched atoms. For example, in a NiPt-containing compound material, Ni atoms are dipped and / or selectively etched from the NiPt compound to form a nanopore structure containing nanopores. The nanopores will have a diameter sufficient to receive Ni atoms.

[0112] The support material may include dopants, including but not limited to nitrogen, phosphorus, sulfur, boron, molybdenum, iron, chromium, cobalt, copper, or combinations thereof. The support material may include doped compounds, including but not limited to nitrogen oxides; nitrogen and sulfur compounds; nitrogen and phosphorus compounds; nitrogen and boron compounds; nitrogen and molybdenum compounds; nitrogen and iron compounds; or combinations thereof. Doping can be introduced as trace impurities into the host compound to alter the surface properties of the electrode, including but not limited to electrical properties or electrochemical potential. Dopants may be present in trace amounts, i.e., less than 5%, in the host material. Dopants may include atomic sizes and structures different from those of the host compound, which is why they are called impurities. Doping can be performed within or after the deposition of the compound material. Depending on the dopant material and its concentration, the dopant material may include a reduced cell potential compared to a theoretical minimum of 1.23 V to less than zero. A reduced cell potential allows less power to be applied to the cell, thereby improving the overall efficiency of the electrolyzer. The dopant can improve the efficiency of the electrolyzer system by at least about 10%, about 10% to about 80%, about 20% to about 70%, about 30% to about 60%, about 40% to about 50%, or about 80%.

[0113] By coating dopants onto electrodes, electrode surface properties can be customized to achieve minimal desired potential and / or maximum efficiency. Dopants can be added to electrodes by: co-deposition in sputtered compound material; using reactive gases during sputtering; electrochemical and / or thermochemical addition after immersion and / or selective etching; or combinations thereof. In co-deposition methods, dopants can be deposited onto the electrode simultaneously with other components of the compound material. The dopant can be less than 10% of the compound material. In reactive gas methods, the nitrogen-to-argon ratio can be less than about 30% to diffuse the dopant (e.g., nitrogen) into the electrode simultaneously with the deposition of the main material. With electrochemical doping, dopants, including but not limited to N, P, S, and / or B, can be dissolved / dispersed in an electrolyte solution. Dopants can be incorporated into the electrode and / or compound material by applying a potential to the electrolyte solution. The potential can be at least about 50 mV, about 50 mV to about 1500 mV, about 100 mV to about 1300 mV, about 200 mV to about 1100 mV, about 300 mV to about 900 mV, about 500 mV to about 700 mV, or about 1500 mV. In the case of thermochemical doping, the compound material and the dopant can be placed in a furnace filled with an inert gas, such as argon. By increasing the temperature, the dopant can be assembled, diffused into, and / or added to the compound material. The temperature can be increased to at least about 250 °C, about 250 °C to 900 °C, about 300 °C to 800 °C, about 400 °C to 700 °C, about 500 °C to 600 °C, or about 900 °C to dope the compound material with the dopant. For all methods, the doped electrode can be treated with reagents including, but not limited to, potassium hydroxide (KOH), K-Na-tartrate tetrahydrate, or combinations thereof, followed by deionized water cleaning, nitrogen drying, oven drying, or combinations thereof to form a microporous and / or nanoporous structure. Additionally, for all methods, dopants can be embedded, doped, and / or added to the support material of the compound material.

[0114] Different types of etching methods can be used, including but not limited to: physical etching, including but not limited to reactive ion etching (RIE) and inductively coupled plasma etching; or chemical / electrochemical etching to immerse the sacrificial material. Etching requires contacting the sacrificial material with a substance to remove it. One or more gases can be used as etchants in physical etching. Reagents can be used in chemical / electrochemical etching. Electrodes can be etched by immersion in a bath containing a chemical / electrochemical etchant. The bath composition, operating temperature, time, and applied current can vary depending on the material selected for etching.

[0115] Baths used for chemical / electrochemical etching may include alkaline or acidic solutions, including but not limited to KOH, NaOH, HCl, H₂SO₄, or combinations thereof. The bath may also include additives, including but not limited to buffers, hydrazine, scale inhibitors, etching promoters, or combinations thereof. Buffers may include, but are not limited to, boric acid, borates, or combinations thereof, and may be used to maintain the pH of the bath. Hydrazine may be used to prevent oxidation in baths with low pH values. Scale inhibitors include, but are not limited to, polyphosphates, and may prevent salt precipitation on the electrodes during etching. Etching promoters include, but are not limited to, potassium-sodium-tartrate tetrahydrates, and may accelerate etching in alkaline environments. The bath may be operated at temperatures of at least about 25°C, about 25°C to about 85°C, about 30°C to about 80°C, about 35°C to about 75°C, about 40°C to about 70°C, about 45°C to about 65°C, about 50°C to about 60°C, or about 85°C. Current may be applied to the bath. The current may include direct current, alternating current, pulsed current, or combinations thereof. The applied direct current may be at least about 25 mA / cm². 2 Approximately 25 mA / Cm 2 Approximately 1000 mA / Cm 2 Approximately 50 mA / Cm 2 Approximately 900 mA / Cm 2 Approximately 100 mA / cm 2 Approximately 800 mA / Cm 2 Approximately 200 mA / Cm 2 Approximately 700 mA / Cm 2 Approximately 300 mA / Cm 2 Approximately 600 mA / Cm 2 Approximately 400 mA / Cm 2 Approximately 500 mA / Cm 2 or approximately 1000 mA / Cm 2 .

[0116] An electrolyzer system may include at least one electrode. The electrode may include an anode and / or a cathode. The electrode may be heat-treated to improve performance. Vacuum heat treatment may be applied to the electrode. Vacuum heat treatment may be operated at temperatures of at least about 300°C, about 300°C to about 1000°C, about 400°C to about 900°C, about 500°C to about 800°C, about 600°C to about 700°C, or about 1000°C. Vacuum heat treatment may be operated for at least about 30 min, about 30 min to about 4 hours, about 1 hour to about 3.5 hours, about 1.5 hours to about 3 hours, about 2 hours to about 2.5 hours, or about 4 hours. Heat treatment may include increasing the electrode temperature, maintaining the electrode temperature, and decreasing the electrode temperature. Increasing and decreasing the electrode temperature may be performed at rates of at least about 5°C / min, about 5°C / min to about 20°C / min, about 10°C / min to about 15°C / min, or about 20°C / min.

[0117] Compared to the theoretical minimum voltage of 1230 mV for water splitting at ambient temperature, the actual cell voltage of the electrolyzer system can be less than about 100 mV. For water splitting, the microporous and / or nanoporous structure of the catalyst composition of the electrodes can reduce the cell voltage to 0 mV, i.e., the electrolyzer system can become a self-generating electrolyzer and operate without an applied voltage. By using dopants including but not limited to B and N, the cathode potential can shift towards a more positive value, and the anode potential can shift towards a more negative value. The hydrogen production reaction can become spontaneous, requiring no external power. At low pH values ​​on the cathode side and high pH values ​​on the anode side of the electrolyzer, the voltage for hydrogen reduction becomes much more positive than that for hydrazine or urea oxidation. Low pH values ​​can be at least about 0, about 0 to about 5.5, about 2.5 to about 5, about 2.5 to about 4.5, about 3 to about 4, or about 5.5. High pH values ​​can be at least about 8, about 8 to about 14, about 9 to about 13, about 10 to about 12, or about 14. Then, as long as the salt concentrations on both sides are maintained, hydrogen production becomes thermodynamically favorable and occurs spontaneously. Therefore, nitrogen-assisted hydrogen electrolyzers can operate spontaneously to produce gaseous hydrogen and also generate electricity. Approximately 1 A·cm⁻¹ can be achieved by incorporating metal or mixed metal-metal oxide nanoparticles into the electrodes. -2 High electrolytic cell current density.

[0118] An electrolyzer system may include an anode cell and / or a cathode cell. The total potential of the anode cell is approximately 10 mA·cm⁻¹. -2 At current densities, the voltage can be less than about 250 mV, about 250 mV to about 0 mV, about 225 mV to about 10 mV, about 200 mV to about 50 mV, about 150 mV to about 100 mV, or about 250 mV. The total potential in the cathode cell is about 10 mA•cm. -2At current densities, the values ​​can be less than about 100 mV, about 0 mV to about 100 mV, about 5 mV to about 99 mV, about 10 mV to about 97 mV, about 15 mV to about 95 mV, about 20 mV to about 90 mV, about 30 mV to about 80 mV, about 40 mV to about 70 mV, about 50 mV to about 60 mV, or about 100 mV.

[0119] The cathode and anode can contain the same material composition, i.e., used as a bifunctional electrode, or contain different material compositions, such as used as separate electrodes. Compared to separate electrodes, because the electrode composition is identical, bifunctional electrodes can have enhanced stability, and the risk of galvanic cell coupling and subsequent electrode corrosion and degradation is reduced or avoided. Pt electrodes with a cell voltage of less than 100 mV can serve as a performance benchmark for both the anode and cathode.

[0120] Microstructured and / or nanostructured foams may include microstructured and / or nanostructured catalysts containing metal or mixed metal-metal oxide nanoparticles. Using physical or chemical deposition methods, including but not limited to magnetron sputtering, plasma coating, electrochemical coating, or combinations thereof, metals or mixed metal-metal oxides may be attached to the microstructured and / or nanostructured foams. Metals may include, but are not limited to, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Ru, Pd, Ag, Cd, Hf, Ta, W, Re, Ir, Pt, Au, or combinations thereof. Metal oxides may be oxides made from the aforementioned metals.

[0121] Industrial availability :

[0122] The invention is further illustrated by the following non-limiting embodiments.

[0123] Example 1

[0124] Compound materials are deposited onto a substrate using a sputtering method. After cleaning, the substrate is loaded into a sputtering chamber (various models such as DC, RF, or magnetrons have been successfully tested), reaching ~10 -6 Torr's base pressure (high vacuum). In an argon or argon / oxygen / nitrogen atmosphere (used for depositing metal oxides or nitrogen oxides, such as IrO). x NiN, NiO x At an operating pressure between approximately 3 and 9 m Torr, the primary catalyst and sacrificial material are co-deposited with a sputtering power ranging from 25 to 500 W and a gas volume ranging from 1 to 100 standard cubic centimeters.

[0125] Example 2

[0126] Compound materials are deposited onto a substrate via electrochemical deposition. Several different methods exist. In one aspect, the electrochemical method is accomplished either by using pulsed electrodeposition or by forming a core-shell structure (the sacrificial material acts as the core, and the main catalyst acts as the shell). A thermostat is used to maintain the temperature of the bath used for the electrochemical method. Solutions are freshly prepared using DI water and AnalaR-grade chemicals. Examples of solutions and salts used for electrochemical deposition are given in Tables 1 and 2.

[0127] Table 1. AEM electrode bath compositions.

[0128]

[0129] Table 2: PEM electrode bath composition.

[0130]

[0131] Example 3

[0132] Electrodeposition of materials is performed using DC and pulsed currents via a potentiostat. The current value and time depend on the coating thickness and morphology, as well as the target grain size range. Electroplating times range from 15 minutes to 1 hour. The applied current ranges from 75 mA / cm². 2 Up to 500mA / cm 2 For the pulse method, using t on = 50 S-5000 S, and t off =10 S-1000 S is a square wave.

[0133] Example 4

[0134] Post-processing of compound materials deposited on a substrate involves leaching and doping. Microstructures of the catalyst material are formed by leaching sacrificial materials from the compound material. This process is accomplished through selective etching. In selective etching, only specific materials are etched, while the impact on other materials in the system is negligible.

[0135] Example 5

[0136] Prepare the nickel substrate. Grind nickel powder with ethanol in a ball mill, add two low-molecular-weight and high-molecular-weight polyvinyl alcohol (“PVA”) polymers, a surfactant such as sodium hexametaphosphate, and spray-dry the slip into spherical granular powder. Sieve to a particle size of 20μm-200μm, and uniaxially compact using a punch and die to a pressure of 200N / mm².2 The powder particles were ejected from the mold, placed on a sintering tray, and sintered at 700°C for 2 hours. The resulting porous microstructure had a density of 2.8 g / cm³. 3 Up to 3.4 g / cm 3 The catalyst material is blended into a thick but spreadable slurry and coated onto the surface of a sintered substrate, which is then sintered again to prepare a multilayer structure. The catalyst layer thickness ranges from 1 μm to up to 150 μm, and multiple layers are optionally applied.

[0137] Example 6

[0138] Prepare the metal substrate. Grind the metal powder using a suitable solvent, trioleic acid glyceride, and polyethylene glycol of various molecular weights to produce a product that can be processed in 100 seconds. -1 The slurry was prepared at shear rates ranging from 1 Pa∙s to 4 Pa∙s. The slurry was cast onto nickel foam using a doctor blade technique to form films with thicknesses ranging from 1 μm to 2000 μm. The films were dried in situ, then removed, subjected to a binder burn-off step (dewaxing), and then sintered between 500°C and 1100°C to prepare a porous multilayer structure.

[0139] Example 7

[0140] Prepare a nickel-titanium substrate. A mixture of nickel-based and titanium-based powders is ground together with commercial carrageenan added. Carrageenan is a macromolecular polysaccharide used to form a gel network. While mixing the additives, the ground mixture is heated to 85°C–95°C. Above 60°C, the slurry remains liquid, but below this temperature, it solidifies into a gel over time. The slurry is spread onto a nickel foam (or a similar porous structure) and allowed to cool and solidify. After vacuum drying for several hours, the part is sintered between 500°C and 1100°C.

[0141] The foregoing embodiments can be replicated similarly and successfully by replacing the components and / or operating conditions used in the foregoing embodiments with those generally or specifically described in the embodiments of the present invention.

[0142] Note that in the specification and claims, “about” or “approximately” means within twenty percent (20%) of a given amount or value.

[0143] Embodiments of the invention may include each combination of features disclosed herein independently of each other. Although the invention has been described in detail with particular reference to the disclosed embodiments, other embodiments may achieve the same results. Variations and modifications of the invention will be apparent to those skilled in the art, and all such modifications and equivalents are intended to be covered in the appended claims. The full disclosure of all references, applications, patents, and publications cited above is incorporated herein by reference. Unless specifically stated above as “essential,” various components or their interrelationships are not essential for the operation of the invention. Rather, the desired results can be achieved by substituting the various components and / or reconfiguring their interrelationships.

Claims

1. A system for electrolyzing a solution, the system comprising: a first vessel in communication with at least one electrolyzer stack, the electrolyzer stack comprising: at least one bipolar electrode, the bipolar electrode comprising: a bipolar plate; a porous transport layer; and a catalyst; the bipolar plate, the porous transport layer, and the catalyst fused together into a single component; at least one separator; and a second vessel in communication with the at least one electrolyzer stack.

2. The system of claim 1, further comprising a substrate.

3. The system of claim 2, wherein the substrate supports the catalyst.

4. The system of claim 2, wherein the substrate comprises an electrically conductive material.

5. The system of claim 4, wherein the electrically conductive material comprises iron.

6. The system of claim 2, wherein the substrate comprises an alloy material.

7. The system of claim 6, wherein the alloy material comprises a platinum group metal.

8. The system of claim 2, wherein the substrate comprises a ceramic.

9. The system of claim 1, wherein the bipolar plate is sintered.

10. A method for making a substrate, the method comprising: providing a metal powder; contacting the metal powder with a polymeric binder to form a metal-binder mixture; and sintering the metal-binder mixture.

11. The method of claim 10, wherein the polymeric binder comprises polyvinyl alcohol.

12. The method of claim 10, wherein the polymeric binder comprises polyethylene glycol.

13. The method of claim 10, wherein the polymeric binder comprises carrageenan.

14. The method of claim 10, wherein the metal powder comprises nickel.

15. The method of claim 10, wherein the metal powder comprises titanium.

16. The method of claim 10, further comprising contacting the metal-binder mixture with a metal foam.

17. A substrate, the substrate comprising: a sintered porous structure; an electrically conductive material; an alloy material; and a functional gradient.

18. The substrate of claim 17, wherein the porous microstructure comprises a porosity of about 20% to about 95%.

19. The substrate of claim 17, wherein the substrate comprises a density of about 2.5 g / cm3 to about 3.4 g / cm3.

20. The substrate of claim 17, wherein the electrically conductive material comprises iron. ​ ​